The laws on contempt of court (ex-facie) and freedom of speech and expression in Malaysia / Aimi Syazwani Sarmin and Izyan Darlina Dato' Balia Yusof. - Sarmin, Aimi Syazwani; Balia Yusof, Izyan Darlina (2005)
This project paper deals with the topic of The Freedom of Speech and Expression and the Laws of Contempt of Court in Malaysia, which specifically focused on one category of contempt of court that is ex facie contempt of court. We have decided to embark onto this particular topic because there is no proper and conclusive Act on this matter and because the scope of this offence is too wide and ambiguous which makes it difficult to determine the offender. Since the public is not aware of this offence, they may misuse the true meaning of 'freedom of speech and expression.' This project paper aims to educate and create awareness among the public on the seriousness of this offence and to restore the good name of the judiciary. Therefore, we felt that it is high time for Malaysia to have its own Act on contempt of court. The current position of this law is scattered and we have gathered all the scattered laws in one chapter. This research is a doctrinal or library based research. We have referred to various legislations, books, journal articles and other related materials. However, an interview was also held which has made clear about the position of the proposed bill by the Bar Council oh this matter. With this project paper, we hoped that the necessary actions would be taken as soon as possible for Malaysia to have its own Contempt of Court Act. We also hoped that our research will help the readers to understand the nature of this offence.